Anti-inflarnmatory activity of Urera baccifera(Urticaceae) in Sprague-Dawley rats - Badilla, Beatriz (Universidad de Costa Rica, 1999)
On a preliminary test, anti-inflammatory and analgesic dose-related activities on rats were observed for the aqueous fraction of Urera baccifera; this extract was bioassay-guided fractionated and the final aqueous fraction was used according the ethnobotanical use. Carrageenan-induced edema (n=6), was used as an assay in the fractionating process. The anti-inflammatory and antinociceptive properties of the final aqueons fraction were studied using in vivo models. For the anti-inflammatory activity rat paw edema (n=6), pleurisy induced by carrageenan (n=6) and ear edema induced by topical croton oil (n=6) models were used, and tail-fIick test (n=6), abdominal constrictions induced by acetic acid (n=6), and formalin test (n=6), were used for the alltillociceptive activity. The tests perfonned showed an inhibition effeet on !eukocyte rnigration, and a reductioll on pleural exudate, as well as dose-dependant peripheral analgesic activity, al a range of 25-100 mglk:g i.p. The final aqueous fraction contains most of the anti-inflammatory activity of the plant U. baccifera. A possibJe mechanism of action is discussed and based on the results we conclude that this plant has a potential. for both anti-inflammalory and analgesic activity al the c1inical level.